2020
DOI: 10.1016/j.earscirev.2020.103354
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage mid-Brunhes climate transition and mid-Pleistocene human diversification

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 176 publications
(270 reference statements)
1
59
0
Order By: Relevance
“…On the CLP, the prominent paleosol S5 developed during MIS15‐13 (Guo et al., 1998), and it can be readily correlated with LL‐3 in the WEDP02 drill core (Wang et al., 2015). Multiproxy indicators of loess records from the CLP also showed that the intensified ASM precipitation and temperature after 600 ka (Ao et al., 2020; Guo et al., 1998; Meng, et al., 2018; Sun et al., 2010). In addition, the lacustrine environment formed or further enlarged in the inland deserts of northern China including Tengger Desert (Li et al., 2014), Badain Jaran Desert (Gao et al., 2006; Wang et al., 2015), Gobi Desert (Li et al., 2017), and Ulan Buh Desert (Li et al., 2015) during the interglacial intervals from MIS15‐13, suggesting the intensification of ASM.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…On the CLP, the prominent paleosol S5 developed during MIS15‐13 (Guo et al., 1998), and it can be readily correlated with LL‐3 in the WEDP02 drill core (Wang et al., 2015). Multiproxy indicators of loess records from the CLP also showed that the intensified ASM precipitation and temperature after 600 ka (Ao et al., 2020; Guo et al., 1998; Meng, et al., 2018; Sun et al., 2010). In addition, the lacustrine environment formed or further enlarged in the inland deserts of northern China including Tengger Desert (Li et al., 2014), Badain Jaran Desert (Gao et al., 2006; Wang et al., 2015), Gobi Desert (Li et al., 2017), and Ulan Buh Desert (Li et al., 2015) during the interglacial intervals from MIS15‐13, suggesting the intensification of ASM.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, numerous records suggested that this enhancement not only occurred in the ASM region, Indian, and African summer monsoons circulation also clearly intensified and Greenland, European, and North American continents all get warmer than prior time during MIS13‐15 stages, signaling a warmer Northern Hemisphere (Ao et al., 2020; Shi et al., 2020; Yin & Guo, 2008) which contrast with the cooler Southern Hemisphere during this time (Ao et al., 2020; Guo et al., 2009). This strong asymmetry of hemispheric climates may modulate the position of the intertropical convergence zone (ITCZ) and land‐sea thermal contrasts and finally intensify the North Hemispheric monsoon circulations (Ao et al., 2020; Guo et al., 2009). Model simulations further confirm this hypothesis, which indicated that when Greenland ice sheet is absence and a large Antarctic ice sheet is obtained, there is an enhancement of ASM precipitation up to ∼7%, consistent with the results by proxy reconstructions (Shi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MIS 11 interglacial was characterized by millennial-scale oscillations, particularly in the Northern Hemisphere, and was a significantly unstable period in northwestern China [43,44]. Both of these climatic conditions—warming and instability—have historically been associated with population movements [4547], and models linking hominin variability to climatic instability have been proposed for Middle Pleistocene Europe [48] and for eastern Eurasia and Africa, particularly with respect to lineage diversification [49].…”
Section: Introductionmentioning
confidence: 99%